Identification of influenza urban transmission patterns by geographical, epidemiological and whole genome sequencing data: protocol for an observational study - Andreas Buser; Sarah Tschudin-Sutter; Adrian Egli; Claudia Saalfrank; Nina Goldman; Myrta Brunner; Yvonne Hollenstein; Thomas Vogel; Noémie Augustin; Daniel Wüthrich; Helena M.B. Seth-Smith; Elisa Roth; et al. (BMJ Open)
Introduction Urban transmission patterns of influenza viruses are complex and poorly understood, and multiple factors may play a critical role in modifying transmission. Whole genome sequencing (WGS) allows the description of patient-to-patient transmissions at highest resolution. The aim of this study is to explore urban transmission patterns of influenza viruses in high detail by combining geographical, epidemiological and immunological data with WGS data.Methods and analysis The study is performed at the University Hospital Basel, University Children’s Hospital Basel and a network of paediatricians and family doctors in the Canton of Basel-City, Switzerland. The retrospective study part includes an analysis of PCR-confirmed influenza cases from 2013 to 2018. The prospective study parts include (1) a household survey regarding influenza-like illness (ILI) and vaccination against influenza during the 2015/2016 season; (2) an analysis of influenza viruses collected during the 2016/2017 season using WGS—viral genomic sequences are compared with determine genetic relatedness and transmissions; and (3) measurement of influenza-specific antibody titres against all vaccinated and circulated strains during the 2016/2017 season from healthy individuals, allowing to monitor herd immunity across urban quarters. Survey data and PCR-confirmed cases are linked to data from the Statistics Office of the Canton Basel-City and visualised using geo-information system mapping. WGS data will be analysed in the context of patient epidemiological data using phylodynamic analyses, and the obtained herd immunity for each quarter. Profound knowledge on the key geographical, epidemiological and immunological factors influencing urban influenza transmission will help to develop effective counter measurements.Ethics and dissemination The study is registered and approved by the regional ethics committee as an observational study (EKNZ project ID 2015–363 and 2016–01735). It is planned to present the results at conferences and publish the data in scientific journals.Trial registration number NCT03010007.